2018
DOI: 10.1016/j.jsha.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the application of treatment Panel III and American College of Cardiology/American heart Association guidelines for blood cholesterol treatment in Saudi Arabia

Abstract: The eligibility for statin therapy was much higher when applying the ACC/AHA guideline as compared to ATP-III guideline. Applying the recent ACC/AHA dyslipidemia guideline increased the number of patients eligible for statin therapy to approximately two folds. This would be associated with a substantial increase in cost and possibly side effects. The concerns surrounding the ACC/AHA guideline should be addressed at the national level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several studies presented the major explanations for statin refractoriness reported by healthcare practitioners, and patients were concerned about adverse events [12,[28][29][30][31][32][33]. Rosenson, R. S 2016 stated that evaluation of potential adverse events requires validated tools to differentiate between statin-associated adverse events versus nonspecific complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies presented the major explanations for statin refractoriness reported by healthcare practitioners, and patients were concerned about adverse events [12,[28][29][30][31][32][33]. Rosenson, R. S 2016 stated that evaluation of potential adverse events requires validated tools to differentiate between statin-associated adverse events versus nonspecific complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies presented the major explanations for statin refractoriness reported by healthcare practitioners, and patients were concerns about adverse events (9,(22)(23)(24)(25)(26)(27). Rosenson, R. S ( 2016) stated that evaluation of potential adverse events requires validated tools to differentiate between statin-associated adverse events versus nonspeci c complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide studies conducted in the United States found that approximately 15%–40% of prescribed statins adhered to the most recent guidelines, particularly the latest ACC/AHA Guideline ( 12 , 13 ). In Saudi Arabia, the adherence rate ranged from 10% to 75%, whereas in Malaysia, it ranged between 40% and 50% ( 14 , 15 ). The adherence rates to guidelines differ across countries.…”
Section: Introductionmentioning
confidence: 99%